Dreaming of Remoteness, Coping with Emptiness in Post-Lockdown (Under)Tourism Scenarios for the Inner Areas of Southern Italy: a Fieldwork Based Reflection - Cocco, Emilio; Mines, Anna Farrell; Salvatore, Rita (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
From the end of 1970s and the neo-liberal shift in world politics and economics, inner areas of Italy have faced an apparently endless crisis. However, the sudden outbreak of the Covid-19 crisis could provoke an unexpected U-turn. Nowadays, the physical and social remoteness of inner areas work as an attraction for people in search for authentic experiences in food, nature and cultural heritage, outside the standard tourist offer and within the framework of “under-tourism”. However, the “imagined remoteness” that drives the public and academic conversation towards the tourist seduction of the inner areas could be misleading for the simple fact that it is “imagined”. Not many people know what it means to live in a remote area, where social and physical distances are huge and the basic services scarce. Thus, the success of post-lockdown tourism strategies centered on inner areas would depend on the positive matching between the needs of the “new” tourism business and the ones of “new” destinations. In this article, we propose a possible interpretation of the above-mentioned challenge, based on the elaboration of data collected during a three-month field work conducted in several small towns of the Basilicata and Calabria regions (Piccole Dolomiti Lucane Regional Park and the Pollino National Park). Our analysis aims to give a more realistic picture of the notions of emptiness and remoteness by assessing the degree of compatibility and the semantic distance between the expectation of the tourism business and the needs of the inner areas.